Between Efficiency And Risk: Data Security in Digital Transportation And the Legal Liability of Platform Providers - Krismiyarsi; Siti Mariyam; Mahmuda Pancawisma Febriharini; Hadi Karyono (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2026)
The era of digitalization has revolutionized the transportation sector, both air and land, by bringing operational service efficiency and transaction practicality for consumers. However, this massive digital transformation poses serious challenges regarding cybersecurity vulnerabilities and the protection of users' personal data privacy. This study aims to examine the legal protection of digital personal data of ride-hailing users in Indonesia and to analyze the responsibility of application provider companies for potential data protection failures. Through a normative legal approach, the study indicates that legal protection for consumers' digital privacy remains weak. This weakness is driven by specific regulatory gaps, the implementation of standard clauses that disadvantage consumers by shifting liability, and the storage of data outside Indonesia's legal jurisdiction which complicates oversight. Furthermore, companies often claim to be merely technology platform providers, effectively positioning themselves as having no direct responsibility for consumer losses, including the potential misuse of data by third parties such as driver-partners. In conclusion, specific regulations and comprehensive legal mechanisms are urgently needed to effectively ensure the protection of users' privacy rights in the digital era.